Funding stability and the pricing of retail rates: Evidence from Turkish banking sector - Koray Alper; Tanju Çapacıoğlu (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper documents how a system wide deterioration in funding quality, which we argue to be underpinned by macroeconomic conditions, can have a substantial effect in the pricing of deposit and loan rates. The study is motivated by a puzzling observation from Turkish banking system. During 2015-2016, retail rates of Turkish banks displayed a persistent upward trend when the policy and money market rates remained unchanged. We conjecture that the underlying reason was the continued deterioration in the structural liquidity positions of Turkish banks, reflected as rising loanto-deposit ratios (LDR). Our results show that in the presence of increasing pressures from worsening funding quality, banks with high LDRs tried to attract more deposits while trying to slow down loan growth rates. To this end, these banks offered higher rates to deposits, particularly, to more stable deposit types. Similarly, evidence suggest that, on the loans side, banks with worse funding quality raised the rates more. As expected, banks increased the rates for the clients/segments where they have more market power. On the other side, despite the increasing pressures on interest rate margins, high LDR banks don't seem to have opted for risky loans.
Keywords: D22; E43; G21; 330; Retail rates; banks; financial stability; macro-financial linkages